Cataloguing discrepancies : the printed York Breviary of 1493 - Hughes, Andrew, 1937-2013 (University of Toronto Press, 2011)
Based on the discrepancies and errors in the existing catalogues of medieval liturgical books, many of which repeat erroneous information for generations, the authors illustrate the defects, problems, and opportunities encountered when technologies of the fifteenth and the twenty-first centuries converge. Not only questioning existing bibliographical practices, Cataloguing discrepancies suggests practical means for improvements to the future description of early printed books of this kind--Book Jacket.